Sustainability-Oriented Entrepreneurship: Examining the Role of Green Innovation and Stakeholder Engagement in Business Growth - Sihite, Mislan; Ma'rifah, Ma'rifah; Saifuddin, Sendy Salsabla; Damayanti, Yenie Eva; Siagian, Ade Onny (International Journal of Business, Law, and Education, 2026)
This study investigates the role of green innovation and stakeholder engagement in driving business growth within sustainability-oriented entrepreneurial firms. With increasing environmental and social pressures, entrepreneurs are challenged to integrate sustainability into their core business strategies while achieving competitive advantages. Using a quantitative approach, data were collected from 250 sustainability-oriented entrepreneurs and managers in small and medium-sized enterprises (SMEs) through a structured survey. Descriptive statistics, reliability analysis, correlation, and regression analyses were conducted to examine the relationships among green innovation, stakeholder engagement, and business growth. The results indicate that both green innovation and stakeholder engagement have significant positive effects on business growth, with evidence of synergistic interaction between the two factors. These findings underscore the strategic importance of sustainability-oriented practices, highlighting that environmental innovation and active stakeholder collaboration can simultaneously enhance firm performance and societal value. The study contributes to theory by integrating resource-based and stakeholder perspectives in entrepreneurial sustainability and offers practical guidance for entrepreneurs and policymakers seeking to achieve economic success while addressing environmental and social challenges.